Beneficial Fruit-Derived Phytochemicals in Treating Alzheimer’s Disease – A Review - Yurida Ni'ma Annisa; Vania Amanda Samor; Muthi Ikawati; Nunung Yuniarti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
Fruits, as a major source of nutrition have been investigated for their emerging evidence of several neuroprotective activities beneficial to Alzheimer’s disease (AD). This paper discusses recent evidence suggesting several fruit-derived bioactive substances that possess anti-AD activity. The original articles from 2011–2022 were collected from Pubmed and Scopus with related keywords and filtered. Several fruit constituents have shown significant inhibitory action against β-amyloid and tau hyperphosphorylation, either directly or indirectly via secretase inhibition. Some were also found to be cholinesterase inhibitors with specific antioxidative roles, disruptors of the neuroinflammation system, and promoters of neurogenesis and the neurogenic process. Many fruit phytochemicals remarkably alter the capability defects shown in AD animal models, such as catechin, nobiletin, and alpha-mangostin. Therefore, further investigations exploring a certain bioactive isolate or formulated dosage form and its mechanism of action are necessary to provide effective prevention and supplementary treatment for AD.